Self-assessed vs. statistical evidence of racial discrimination: The case of indigenous Australians - Duncan, Alan; Mavisakalyan, Astghik; Tarverdi, Yashar (Routledge, 2018)
This paper provides new insights on the labour market discrimination faced by indigenous Australians - one of the most disadvantaged indigenous populations in developed countries. Combining two large, nationally-representative datasets, we decompose the employment gap between indigenous and non-indigenous populations as of 2014-2015, and show that differences in characteristics between the two groups account for only 43% of the employment gap for females, and 23% of the gap for males. We then demonstrate that statistical measures are positively related to discrimination reports of females and negatively related to discrimination reports of males. Our findings underscore the importance of improving transparency in employment processes for addressing the issue of disadvantage of racial minorities.